In the grey zone: large-scale assessment-based activities betwixt and between policy, research and practice. Issue 1 (2nd January 2017) - Pettersson, Daniel; Popkewitz, Thomas S.; Lindblad, Sverker
ABSTRACT: This paper elaborates on a systematic research review containing 11, 000 articles on international large-scale assessment (ILSA) research. Several activities operating under the 'formal radar' of science and governmental policy are observed, which we analytically name 'grey zone' activities. These activities are historicised, presented and discussed. An analytical division into three different reasons for performing the activities is made: an entrepreneurial policy reason, an entrepreneurial profitable reason and an appurtenance reason. This division highlights some of the actors in the educational grey zone. The paper is theoretical and elaborative, and contains examples of the activities that can be found in a grey zone.